Pandangan Tokoh Agama Non Islam Terhadap Gagasan Gus Dur Tentang Pluralisme - Maulana Yusup; Zulkifli Lubis; Noor Rachmat (Jurnal Studi Al-Qur'an, 2017)
The researcher concludes that the notion of pluralism with Gus Dur perception of non-Muslim religious leaders can diteriam (comfortable), that Gus idea of pluralism is inseparable from democracy, culture, justice and inklusifisme . And of the concept of democratic pluralism Gus Dur, culture, justice and inklusifisme be known, Praise be to Allaah than these four concepts is a major theme of thinking Gus Dur is human. This study aims to describe and analyze the views of non-Muslim religious leaders to the idea of Gus Dur on religious pluralism.